Prefabricated wood i-joist: araucaria hunsteinii flanges and oriented strand board web with l-butt joint / Wan Mohd Nazri Wan Abdul Rahman ... [et al.] - Wan Abdul Rahman, Wan Mohd Nazri; Md. Hassan, Muhammad Nadmin; Ahmad, Abdul Jalil; Muhammed, Suhaimi; Md. Khaidzir, Md. Omar (2002)
I-joist is a modern wood product that can be used as a housing construction material such as roof and floor systems. It is a system that consists of flanges and web components, and both have to work together as a system in order to match the strength property of solid wood beam. This system was obtained by using Araucaria hunsteinii as solid wood flange and oriented strand board (OSB) web material with L-butt joint. The results showed that the average value of modulus of rupture (MOR) was 23.2 MPa and the average value of modulus of elasticity (MOE) was 11,454.0 MPa. In all cases, failures in the I-joist specimens studied were either in tension or in compression and failure occurred at the web joints. The L-butt jointing techniques encourage to the usage of off-cuts from related wood-based industries thus leading to the optimum utilisation of timber.